2017
DOI: 10.1007/s10147-017-1200-4
|View full text |Cite
|
Sign up to set email alerts
|

A double-blind randomized phase II dose-finding study of olanzapine 10 mg or 5 mg for the prophylaxis of emesis induced by highly emetogenic cisplatin-based chemotherapy

Abstract: UMIN000014214.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 18 publications
5
47
2
1
Order By: Relevance
“…[ 13 ] Another research, a double-blind randomized phase II study of olanzapine 10 mg versus 5 mg for emesis induced by highly emetogenic chemotherapy (HEC) completed. [ 18 ] They conducted the study to base on olanzapine in combination with standard antiemetic treatment (aprepitant, palonosetron, and dexamethasone). Therefore, we explore the efficacy and safety of the dose of 5 mg olanzapine with palonosetron and dexamethasone for the prevention of HEC in lung cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…[ 13 ] Another research, a double-blind randomized phase II study of olanzapine 10 mg versus 5 mg for emesis induced by highly emetogenic chemotherapy (HEC) completed. [ 18 ] They conducted the study to base on olanzapine in combination with standard antiemetic treatment (aprepitant, palonosetron, and dexamethasone). Therefore, we explore the efficacy and safety of the dose of 5 mg olanzapine with palonosetron and dexamethasone for the prevention of HEC in lung cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…Two different olanzapine dosages were used in this review, and subgroup analysis shows that both doses (10 mg and 5 mg olanzapine) provided comparably significant improvement in acute and delayed CINV. The phase 2 trial by Yanai et al 14 found that 5 mg of olanzapine had a higher complete control in delayed CINV compared with 10 mg (83.1% vs 77.6%). Because olanzapine may lead to central nervous system depression, especially in elderly and debilitated patients,33 5 mg per day of olanzapine should be more suitable for cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…The National Comprehensive Cancer Network (NCCN) guidelines for antiemesis (version 1.2019) also recommend olanzapine combined with a 5-HT3 RA plus dexamethasone after NK-1 RA for high and moderate emetogenic chemotherapy; however, 5 mg per day was considered only when 10 mg per day caused serious sedation. RCTs12 13 demonstrated 5 mg oral olanzapine per day to be effective, and a randomised phase 2 dose-finding study14 even revealed that 5 mg had a higher complete control in delayed CINV compared with 10 mg (83.1% vs 77.6%). Meta-analysis15 also found that both 5 mg and 10 mg olanzapine exhibited similar efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…В 2017 г. Янай Т. (Yanai T.) и соавторы опубликовали результаты рандомизированного двойного слепого исследования II фазы, посвященного сравнению эффективности дозы оланзапина 5 и 10 мг в сочетании со стандартной терапией апрепитантом, палоносетроном и дексаметазоном [24]. Оланзапин назначался в 1-4-й дни курса, остальные препараты -в стандартных терапевтических дозах.…”
Section: рекомендованные режимы применения оланзапинаunclassified